Consumer Behaviour in the Smartphone Market in Vietnam - Wollenberg, Alexander; Thuong, T. (International Association of Computer Science and Information Technology, 2014)
This paper discusses the factors involved in deciding on a particular type and brand of smartphone in Ho Chi Minh City, Vietnam’s largest city. As the 3rd-largest economy in ASEAN, Vietnam may provide a useful insight for marketing experts and producers of smartphones of consumer behaviour in emerging markets. First, the study uses demographic factors and independent variables of Advertising, Perceived Quality, Word of Mouth, and Price and their impact on Brand Perception and the resulting strength of brand perception on the purchasing decision (dependent variable). Second, the study also connects each independent variable directly to the Purchasing Decision and thus compares the importance of each independent variable individually on the purchasing decision to frame the relative importance of brand perception.